2004
DOI: 10.1093/ps/83.12.1959
|View full text |Cite
|
Sign up to set email alerts
|

Thermal manipulations during broiler chick embryogenesis: effects of timing and temperature

Abstract: This study aimed at elucidating the effects of thermal manipulation (TM) during different periods of embryogenesis on hatchability, body weight, and thermoregulation of Ross chicks at hatch, and on the chick's ability to cope with thermal challenge (TC) at 3 d of age. Control embryos were incubated at 37.8 degrees C and 56% RH, whereas the TM embryos were treated for 3 h at 39.5 (1) or 41.0 degrees C (2) and 65% RH, during early embryogenesis (EE), E8 to E10, and late embryogenesis (LE) at E16 to E18. At hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 15 publications
10
93
1
10
Order By: Relevance
“…This result was consistent with the results of both long-term hightemperature, environment-treated studies (Piestun et al, 2008;Akşit et al, 2010;Yalçin et al, 2010) and short-term high-temperature, environment-treated studies (Moraes et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007). By contrast, there are few studies suggesting that the high temperature applied during incubation has an effect on the hatching weight in broilers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result was consistent with the results of both long-term hightemperature, environment-treated studies (Piestun et al, 2008;Akşit et al, 2010;Yalçin et al, 2010) and short-term high-temperature, environment-treated studies (Moraes et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007). By contrast, there are few studies suggesting that the high temperature applied during incubation has an effect on the hatching weight in broilers.…”
Section: Discussionsupporting
confidence: 88%
“…However, some researchers (Collin et al, 2005;Yahav and Tzschentke, 2006;Halle and Tzschentke, 2011) suggested Thermal manipulations during chicken embryogenesis that this situation can vary depending on the degree of temperature, the application time and the period. Yahav et al (2004a), who applied 39.5°C and 65% relative humidity on the 16 to 18th day of incubation, reported that the hatchability was 97.88% and this rate was 5.39% higher than the C group. The researchers suggested that a short-term high-temperature environment application has a positive effect on hatchability.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A main advantage is that the embryonic development can be easily manipulated. Different endogenic factors with an impact on the avian embryogenesis have been investigated including the oxygen concentration (LeonVelarde and Monge, 2004;Chan and Burggren, 2005; -E-mail: Carsten.Werner@tiho-hannover.de Mortola and Labbe, 2005), the light colour (Rozenboim et al, 2003;Halevy et al, 2006) or the temperature around the brooding eggs (Christensen et al, 2001;Gauly et al, 2001;Von Blumroder and Tonhardt, 2002;Maltby et al, 2004;Tonhardt et al, 2004;Yahav et al, 2004a and2004b;Lourens et al, 2005;Collin et al, 2007;Hammond et al, 2007;Piestun et al, 2009). Direct manipulations include the in-ovo injection of growth hormones or factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…embryonic day (ED) 4 to 7, ED 8 to 12, ED 8 to 10, ED 16 to 18) and sampling times before and after hatch of the animals (e.g. ED 18, 4 day, 25 day and 35 day post-hatch) (Maltby et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007;Hammond et al, 2007;Piestun et al, 2009). Considering these publications -especially of this Maltby et al (2004) who showed that higher incubation temperatures between ED 9 and 12 in turkeys increases the MFN, the aim of this study was to investigate, how a higher incubation temperature between ED 7 and 10 -an important period of primary (embryonic) and secondary (foetal) myotube formation (Miller and Stockdale, 1986) -influences muscle development and/or structure in broiler post-hatch.…”
Section: Introductionmentioning
confidence: 99%